Clinical outcomes after 4.5 years of eliglustat therapy for Gaucher disease type 1: Phase 3 ENGAGE trial final results. Issue 9 (11th July 2021) - Mistry, Pramod K.; Lukina, Elena; Ben Turkia, Hadhami; Shankar, Suma P.; Baris Feldman, Hagit; Ghosn, Marwan; Mehta, Atul; Packman, Seymour; Lau, Heather; Petakov, Milan; Assouline, Sarit; Balwani, Manisha; et al.
Abstract: Eliglustat, an oral substrate reduction therapy, is approved for eligible adults with Gaucher disease type 1. In the Phase 3 ENGAGE trial of previously untreated adults with Gaucher disease type 1, eliglustat‐treated patients had statistically significant improvements in organ volumes and hematologic parameters compared with placebo in the 9‐month primary analysis. We report final outcomes by time on eliglustat among all patients who participated in the ENGAGE trial and extension. No patient deteriorated clinically or withdrew due to adverse events; 39/40 patients entered the open‐label extension period and 34/40 (85%) remained in the trial until completion or switching to commercial eliglustat after its approval (2.3–6 years). Clinically meaningful improvements in Gaucher disease manifestations were seen in all patients concomitant with reductions in pathological lipid substrate levels (glucosylceramide and glucosylsphingosine). Among patients with 4.5 years of eliglustat exposure, mean spleen volume decreased by 66% (from 17.1 to 5.8 multiples of normal [MN], n = 13), mean liver volume decreased by 23% (from 1.5 to 1.1 MN, n = 13), mean hemoglobin increased 1.4 g/dl (from 11.9 to 13.4 g/dl, n = 12), mean platelet count increased by 87% (from 67.6 to 122.6 × 10 9 /L, n = 12), median chitotriosidase decreased by 82% (from 13 394 to 2312 nmol/h/ml, n = 11), median glucosylceramide decreased by 79% (from 11.5 to 2.4 μg/ml, n = 11), median glucosylsphingosine decreased by 84% (from 518.5 to 72.1 ng/ml, n = 10), and mean spine T‐score increased from −1.07 (osteopenia) to −0.53 (normal) ( n = 9). The magnitude of improvement in Gaucher disease manifestations and biomarkers over time was similar among the full trial cohort. Eliglustat was well‐tolerated and led to clinically significant improvements in previously untreated patients with Gaucher disease type 1 during 4.5 years of treatment.